THE RELATIONSHIPS BETWEEN LANGUAGE LEARNING BELIEFS, LEARNING STRATEGY USE, AND LANGUAGE PROFICIENCY OF INDONESIAN EFL HIGH SCHOOL STUDENTS - Taufiqurrohman, Asep (2016)
This study aimed to investigate the relationships between learners' beliefs, learning strategies, and language proficiency because learners' beliefs and learning strategies are important aspects in learners' progress, therefore understanding these aspects might help learners to improve their learning outcome. This study used correlational method and involved 67 Indonesian high school students. The data about learners' beliefs was collected through Beliefs about Language Learning Inventory (BALLI), the data about learners' learning strategies was collected through Strategy Inventory for Language Learning (SILL), and the data about learners' proficiency was collected from test scores obtained from the English teacher. These data were analyzed using Spearman's rank correlation coefficient. The results show that the relationship between learners' beliefs and learning strategies is positive and significant, while the relationship between learners' beliefs and proficiency, as well as between learning strategies and proficiency, is positive but not significant.;--- Penelitian ini bertujuan menyelidiki hubungan antara kepercayaan, strategi belajar, dan kecakapan siswa karena kepercayaan dan strategi belajar siswa adalah aspek penting dalam perkembangan siswa, maka memahami aspek-aspek ini dapat membantu siswa untuk meningkatkan hasil belajar mereka. Penelitian ini menggunakan metode korelasional dan melibatkan 67 siswa SMA Indonesia. Data tentang kepercayaan siswa diperoleh melalui Beliefs about Language Learning Inventory (BALLI), data tentang strategi belajar siswa diperoleh melalui Srategy Invetory for Language Learning (SILL), dan data tentang kecakapan siswa diperoleh dari hasil ulangan yang didapat dari guru bahasa Inggris, Data-data ini dianalisis menggunakan Spearman's rank correlation coefficient. Hasilnya menunjukkan bahwa hubungan antara kepercayaan dan strategi belajar siswa positif dan signifikan, sedangkan hubungan antara kepercayaan dan kecakapan siswa, serta antara strategi belajar dan kecakapan siswa, positif tetapi tidak signifikan.